Pengembangan Video Pembelajaran Fisika Channel Youtube Berbantu Aplikasi Powtoon pada Materi Suhu dan Kalor - Amirul Anam; Widya Wati; Nur Asiah (Pendidikan Fisika Universitas Nurul Huda, 2020)
This research aims to produce physics learning videos on the YouTube channel assisted by Powtoon application on temperature and heat subject that meets valid criteria. To make learning interesting, learning videos need to be developed, one of the interesting learning videos is the Physics Learning Video on the YouTube Channel assisted by the Powtoon application. The research method used in this research is Research and Development with the Borg and Gall model. Based on the results of the research, the validity score of the Learning Video assisted by the Powtoon application based on expert judgment is in very valid criteria, with the percentage of validation from media experts is 84%, from material experts 92%, and IT experts 89%. Teachers and students responded positively to the attractiveness of Learning Videos assisted by the Powtoon application as a learning media, with the percentage of teacher response scores reaching 85%, small group tests 79%, and field test results 82%. Development of Learning Videos assisted by the Powtoon application is very valid and gets positive responses to be used as learning media.